2006
DOI: 10.1118/1.2358195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different commercial FFDM units by means of physical characterization and contrast‐detail analysis

Abstract: The purpose of this study was to perform a complete evaluation of three pieces of clinical digital mammography equipment. Image quality was assessed by performing physical characterization and contrast-detail (CD) analysis. We considered three different FFDM systems: a computed radiography unit (Fuji "FCR 5000 MA") and two flat-panel units, the indirect conversion a-Si based GE "Senographe 2000D" and the direct conversion a-Si based IMS "Giotto Image MD." The physical characterization was estimated by measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 30 publications
(29 reference statements)
8
61
1
1
Order By: Relevance
“…( 4 , 5 ) This decrease in MTF with respect to the previous GE model may be understood according to the changes introduced in the new system. Specifically, the CsI:Tl scintillator thickness is increased in order to enhance DQE at low spatial frequencies.…”
Section: Resultsmentioning
confidence: 90%
“…( 4 , 5 ) This decrease in MTF with respect to the previous GE model may be understood according to the changes introduced in the new system. Specifically, the CsI:Tl scintillator thickness is increased in order to enhance DQE at low spatial frequencies.…”
Section: Resultsmentioning
confidence: 90%
“…Ancak ilave gürültünün karakteristiği ve frekansı hakkında herhangi bir bilgi elde edilememektedir [6]. Bir dijital görüntüdeki kuantum gürültüsüne ek gürültü kaynaklarının varlığının saptanmasına yönelik literatürde çeşitli yöntemler önerilmiştir [5][6][7][8][9][10] …”
Section: Gi̇ri̇ş (Introduction)unclassified
“…In the past few years, the most recognized and comprehensive metric of image quality performance for digital radiographic and mammographic systems has been the detective quantum efficiency (DQE), a measure of the efficiency of a detector when using the input signal-to-noise ratio (SNR) provided by a limited number of x-ray photons to form an image at a certain exposure or dose level. With measurement methods largely standardized (1)(2)(3)(4)(5), a number of studies have reported the variations in DQE performance of these imaging systems (6)(7)(8)(9).…”
Section: Rsna 2008mentioning
confidence: 99%